Experimentações tradutológicas na obra Cuchulain of Muirthemne de Lady Gregory. - Alencar, Hygor Rodrigues Brasil de (Universidade Federal do Tocantins, 2022)
The present work aims at promoting the debate on the field of translation, more specifically Literary Translation, followed by an experiment in translation using those concepts to analyse said experiment. The focus of our translation is a tale within the book Cuchulain of Muirthemne by Lady Augusta Gregory to the Portuguese language. Initially, it is a bibliographical work, briefly revising the relevant literature on Translation Studies, Lady Gregory’s work and impact to the Irish Nationalist Movement in the beginning of the 20th Century. Afterwards, the translation activity is exemplified in practice, bringing to the research an artistic approach. For such purpose, our theoretical framework addresses reflections on translation as a scientific pursuit (Edwin Gentzler), specificities of Literary Translation (Paulo Henriques Brito) and thoughts on Post-Colonial Translation (Lawrence Venuti e Susan Bassnett). Next, we will present research on the translated original, its history and context, as well as the literary scene that produced it. Finally, we will present our considerations on the process of translation and the results achieved with the final text.